Long-legged flies (Diptera: Dolichopodidae) in the Czech Republic—2. Corindia and Thrypticus - Kejval, Zbyněk; Pollet, Marc (Zootaxa, 2024)
The faunistics of long-legged flies of the genera Corindia Bickel, 1986 and Thrypticus Gerstäcker, 1864 in the Czech Republic (subdivided into Bohemia and Moravia) were investigated. The occurrence of 14 species could be confirmed with 13 in Thrypticus, including Thrypticus bolevensis sp. nov., and one species of Corindia. Six species are recorded from the Czech Republic for the first time: Thrypticus cynicus Drake & Godfrey, 2023, T. intercedens Negrobov, 1967, T. nigricauda Wood, 1913, T. pollinosus Verrall, 1912, T. tarsalis Parent, 1932 and T. virescens Negrobov, 1967; and three other species from Bohemia for the first time: Corindia viridis (Parent, 1932), Thrypticus cuneatus (Becker, 1917) and T. laetus Verrall, 1912. An updated checklist of Corindia and Thrypticus species of the Czech Republic is provided.